Maximal oxygen uptake, total metabolic energy expenditure, and energy cost in swimmers with physical disabilities. (4th July 2019) - Feitosa, Wellington G.; Barbosa, Tiago M.; Correia, Ricardo De A.; Castro, Flávio A. De S
ABSTRACT: The purpose of this study was to assess the maximum oxygen uptake ( V̇ O2max ), the total metabolic energy expenditure ( E ˙ t o t ), and the energy cost ( C ) measured as the speed of V̇O2max in swimmers with physical impairments. Eleven swimmers performed an Nx200-m front crawl test from a low to all-out speed and data were obtained at maximum aerobic power. The oxygen uptake was measured breath-by-breath by a telemetric gas exchange system. The E ˙ t o t was calculated from the aerobic and anaerobic pathways at maximal intensity. The C was obtained by the ratio of the E ˙ t o t and the mean swimming speed. The V̇O2max was 38.2 ± 8.3 mL.kg.min −1, the E ˙ t o t was 191.9 ± 51.7 kJ, and the C was 0.8 ± 0.2 kJ.m −1 . The energy contribution of the aerobic pathway was higher (p < 0.001) than that of both the anaerobic pathways, which were similar (p > 0.05). There was no gender effect on the results of the energy contributions (p > 0.05). The anaerobic lactic pathway contribution was higher in male than in female swimmers (p < 0.05). The V̇O2max and C were higher in swimmers who were less affected by physical impairment. The energy contribution of the aerobic pathways was similar for males and females.